2018
DOI: 10.1186/s12886-018-0787-1
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of myopia and its relation with GDJ2 and RASGRF1 genes in Lithuania

Abstract: BackgroundThis study aimed to assess heritability of myopia in Lithuania and evaluate both genes GJD2 (Gap Junction Protein, Delta 2) and RASGRF1 (RAS protein-specific guanine nucleotide-releasing factor 1) relation with myopia.MethodsIn this study Lithuanian twin population aged between 18 and 40 (n = 460) were examined. Single-nucleotide polymorphisms of the RASGRF1 (rs8027411) and GJD2 (rs634990) genes were assessed by real-time polymerase chain reaction method.ResultsIntrapair correlations for spherical eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Defects in the RASGRF1 gene cause impaired regulation of retinol and muscarinic receptors, resulting in impaired visual development and increased risk of high myopia [16,17]. Kunceviciene et al [18] found that the RASGRF1 gene was associated with the heritability of myopia, in which the rs8027411GT type carriers were 2.7fold more likely to develop myopia, similar to the results of the present study, suggesting that the focus should be on the rs8033417 locus C carriers and timely and efective preventive measures should be given to slow down the development of myopia.…”
Section: Discussionmentioning
confidence: 99%
“…Defects in the RASGRF1 gene cause impaired regulation of retinol and muscarinic receptors, resulting in impaired visual development and increased risk of high myopia [16,17]. Kunceviciene et al [18] found that the RASGRF1 gene was associated with the heritability of myopia, in which the rs8027411GT type carriers were 2.7fold more likely to develop myopia, similar to the results of the present study, suggesting that the focus should be on the rs8033417 locus C carriers and timely and efective preventive measures should be given to slow down the development of myopia.…”
Section: Discussionmentioning
confidence: 99%
“…Similar disruptions are mirrored in zebrafish, where elimination of Cx36 homologs results in delayed responses to threatening stimuli and motor coordination defects . These behavioral defects in animal models lacking a broad class of electrical synapses are exactly what the field of neurodevelopment would expect for genes linked to disease phenotypes (Mas et al, 2004;Hempelmann et al, 2006;Solouki et al, 2010;Li et al, 2015;Kunceviciene et al, 2018). Namely, that many disorders of neurodevelopment result not in large effects with gross dysfunction, but instead are comprised of subtle molecular differences that slightly shift the functional outcomes.…”
Section: Discussionmentioning
confidence: 83%
“…Researchers have found that astigmatism has a strong genetic basis, with astigmatism accounting for 50–60% of the predominant genetic effects compared to additive, common, or unique components [ 20 ]. In one of our publications, it was announced that the heritability of myopia in Lithuania is 0.66 [ 21 ]. However, heritability studies do not determine which genes are relevant to the onset of refractive errors.…”
Section: Discussionmentioning
confidence: 99%